An investigation of materialism and undergraduates' life satisfaction - Ang, Chin Siang; Abu Talib, Mansor (IDOSI Publications, 2011)
Although there have been substantial empirical studies that have investigated the effect of materialism on life satisfaction, the nature of life satisfaction of Malaysian undergraduate students and its relationship with materialism still remain largely ambiguous and warrant an investigation. Against this backdrop, the present investigation attempted to examine the linkage between materialism and satisfaction of life among Malaysian undergraduate students. Data analysis was done based on responses of self-administered questionnaires that were completed by three-hundred and sixty-six students. The questionnaire consisted of inventories that assessed dispositions of materialistic values and perception of life satisfaction in general. Results of the study affirmed that materialism and its three dimensions were statistically correlated to life satisfaction. Interpretably, the greater endorsement of materialistic values as well as the three belief domains of materialism could undermine the feeling of satisfaction with life. From the evaluation of stepwise regression, the inclusion of Possession-defined Success and Acquisition as the Pursuit of Happiness elements successfully accounted for 21.5% of the variance of undergraduates’ life satisfaction. Notably, Possession-defined Success items captured the most variance in undergraduates’ life satisfaction. The findings of this study have important implications for contributing towards intellectual enrichment of a body of research in Malaysian context.